Imaging of gamma photons from activated gold wire using a high-energy gamma camera after irradiation of neutrons from boron neutron capture therapy (BNCT) system. (1st April 2023) - Yamamoto, Seiichi; Hu, Naonori; Kataoka, Jun; Koshikawa, Nanase; Kanai, Yasukazu; Tanaka, Hiroki; Ono, Koji
Abstract: Gold wire is commonly used for quality assurance (QA) of the neutron beam in a boron neutron capture therapy (BNCT) system. It is set in water and irradiated with the neutron beam, and then 412-keV gamma photons from the activated gold wire are measured by a semiconductor detector. Since this procedure takes time and labor, a more efficient method is desired. To reduce the time and labor to measure the radioactivity of an activated gold wire, we carried out imaging of 412-keV gamma photons from the activated gold wire using a developed high-energy gamma camera. After the gold wire was set in the depth direction in a water-filled phantom and irradiated with neutron beams using the BNCT system, gamma photon imaging was conducted with the developed high-energy gamma camera. On the measured image, a depth profile was set to obtain the neutron distribution, and this was compared with the profile sequentially measured with a semiconductor detector. An image of the 412-keV gamma photons was obtained with an imaging time of 1.5 hours. The estimated depth profile of the neutron beam from the gamma camera image closely matched that measured with a semiconductor detector. Imaging of the gamma photons emitted from the activated gold wire was possible, and it offers an efficient method to measure the thermal neutron distribution of the BNCT system. This method has the potential to reduce the time and labor for QA of a BNCT system.